Stevens-Johnson syndrome/toxic epidermal necrolysis spectrum for the rheumatologist - Jyoti Ranjan Parida; Saumya Ranjan Tripathy (Indian Journal of Rheumatology)
Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) represent a spectrum of mucocutaneous manifestations characterized by widespread epidermal and/or mucosal detachment from dermis. It occurs due to Type IV hypersensitivity leading to keratinocyte apoptosis. Many extrinsic and intrinsic defects in the apoptotic pathway have been postulated to result in its dysregulation. The characteristic skin lesions of SJS/TEN include ill-defined, coalescing, red macules with necrotic centers followed by extensive epidermal detachment. Mucosa is involved in up to 90% of cases causing erosions and crusts that may precede or follow skin lesions. Supportive care is the mainstay of treatment and if not started promptly may result in high mortality and morbidity. Although many immunosuppressive drugs have been tried in treatment, no treatment has proven beneficial except cyclosporine which has been shown to retard the progression of SJS/TEN. A patient with SJS/TEN as a presenting feature poses two-fold challenge to a rheumatologist as it could be a manifestation of lupus or side effects of a myriad of drugs used by the rheumatologist.